THE ENERGY DISTRIBUTIONS IN SPECTRA OF STARS IN REGION λλ 320-750 nm - Komarov, N. S.; Arkhipov, M. G.; Belik, S. I.; Depenchuk, E. A.; Dragunova, A. V.; Zakozhurnikova, N. N.; Kantsen, L. E.; Orlova, L. F.; Pereverzentsev, A. F.; Cherkass, A. G.; Chuprina, R. I. (Одеські астрономічні публікації, 2017)
The original energy distributions in Visual region of the spectra of 370 stars were received using the method of electrospectrophotometry.